Leveraging Technology for Gender-Inclusive Governance in Nigeria: Assessing Digital Strategies to Advance Gender Equality (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the role of technology in advancing gender-inclusive governance in Nigeria, with a focus on evaluating digital strategies that can promote gender equality and enhance women's participation in governance. Despite Nigeria’s commitment to international frameworks such as the Beijing Declaration and Sustainable Development Goal 5, systemic gender disparities persist in political representation, economic opportunities, and social inclusion. Traditional policy approaches have often fallen short due to entrenched cultural norms, limited access to resources, and inadequate institutional mechanisms. In response, this research investigates how technological innovations, including e-governance platforms, mobile applications, and data analytics, can serve as transformative tools for addressing these challenges. The study employs a mixed-methods approach, combining quantitative analysis of existing digital initiatives with qualitative insights from interviews with policymakers, civil society actors, and women leaders. Key findings reveal that digital tools have the potential to amplify women’s voices, streamline access to government services, and facilitate evidence-based policymaking through disaggregated data collection. However, significant barriers remain, including the digital gender divide, low levels of digital literacy among women, and infrastructural limitations in rural areas. To address these gaps, the study recommends targeted investments in digital infrastructure, capacity-building programs for women, and the integration of gender-responsive design principles into technological solutions. By leveraging technology strategically, Nigeria can move closer to achieving gender equality and fostering inclusive governance systems that reflect the needs and aspirations of all citizens. This research contributes to ongoing global discussions on the intersection of technology, governance, and gender equity.